ANALISIS PERBANDINGAN KUALITAS LAYANAN JARINGAN 4G LTE TELKOMSEL BERDASARKAN PADA PERIODE WEEKDAY DAN WEEKEND DI KECAMATAN BUNGUS TELUK KABUNG, KOTA PADANG - Mailani, Sri (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid development of 4G LTE technology is often challenged by dynamic traffic patterns, particularly in tourist areas like Bungus Teluk Kabung, Padang. This research aims to analyze and compare the Quality of Service (QoS) of Telkomsel's 4G LTE network during weekday and weekend periods. Data collection was conducted using the drive test method with TEMS Pocket 2 software in dedicated mode to measure key parameters: RSRP, RSRQ, SINR, and throughput. The results indicate a significant difference in network performance between the two periods. While signal coverage (RSRP) remained stable and